HIV testing in patients with end stage renal disease. Issue 6722 (17th February 1990) - Stevens, A; Little, J; Kerr, S; Kilbane, P; Doherty, C
Abstract : One hundred and twenty eight British and Irish nephrologists were questioned about their policy for HIV testing of patients with end stage renal failure being considered for renal replacement therapy. A total of 101 (79%) replied. In the case of candidates for dialysis roughly one third of respondents tested only people they considered at risk of infection with HIV and nearly one fifth considered testing unnecessary. In the case of candidates for transplantation routine HIV testing was carried out by 68 of 100 nephrologists; 22 tested only patients "at risk" and 10 did not test. A positive HIV test result was considered by most but not all respondents (63/86) to exclude patients from transplantation. Twenty four of 88 nephrologists considered that HIV positivity should exclude patients from haemodialysis, but only seven of 87 would exclude such patients from peritoneal dialysis. Similar attitudes pertained for patients with end stage renal failure who refused HIV testing. Testing with the patient's knowledge and consent was the policy of two thirds of nephrologists, but a patient's signature was obtained by only 24 of 88. There should be a consensus on practice for HIV testing of patients with end stage renal failure.